Nilai-Nilai Pendidikan Budi Pekerti Menurut Ki Hadjar Dewantara dan Relevansi dengan Kebijakan Pendidikan Karakter - Zuhri Dwi Apriansah; Deri Wanto (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
The aim of the study was to determine the values ​​of character education according to Ki Hadjar Dewantara and their relevance to character education policies. The benefit of research is to enrich the body of knowledge in the world of education. The research uses a qualitative approach with a narrative biographical research type with a descriptive presentation method. This type of research uses the library research method. The results of the study show that: First, the Values ​​of Character Education According to Ki Hadjar Dewantara in instilling morals in students consist of several components. Second, the current forms of character education policies in Indonesia include Law No. 20 of 2003 concerning the Indonesian National Education System, Law No. 14 of 2005 concerning Teachers and Lecturers, Permendikbud No. 23 of 2015 concerning Growth of Character (PDB), Presidential Regulation no. 87 of 2017 concerning Strengthening Character Education (PPK). Third, the Relevance of Character Education according to Ki Hadjar Dewantara with the Character Education Policy, namely, the Tri Center which consists of family, school, and youth, to become an educator must have severe requirements, namely besides having scientific intelligence, also having a good personality. Regarding educational material adjusted based on the level taken, the moral education method is Momong, Among, and Ngemong.